You are correct. The answer is choice C.
Step-by-step explanation:
We can solve for 'a' like so
![A = ((a+b))/(2)h\\\\2A = (a+b)h\\\\(2A)/(h) = a+b\\\\(2A)/(h)-b = a\\\\a = (2A)/(h)-b\\\\](https://img.qammunity.org/2022/formulas/mathematics/high-school/mywmtraz4s2bwirj0v0xc56bz614dc6cb3.png)
In the second step, I multiplied both sides by 2. Afterward, I divided both sides by h in the third step. Lastly, I subtracted b from both sides to isolate 'a' in step 4. Each step is following PEMDAS in reverse to undo every operation done to variable 'a'.